2021
DOI: 10.3389/fimmu.2021.758227
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Probiotic for Diarrhea: Clostridium tyrobutyricum Protects Against LPS-Induced Epithelial Dysfunction via IL-22 Produced By Th17 Cells in the Ileum

Abstract: Probiotics are clinically used for diarrhea and inflammatory bowel diseases in both humans and animals. Previous studies have shown that Clostridium tyrobutyricum (Ct) protects against intestinal dysfunction, while its regulatory function in the gut needs further investigation and the related mechanisms are still not fully elucidated. This study aims to further verify the protective function of Ct and reveal its underlying mechanisms in alleviating diarrhea and intestinal inflammation. Ct inhibited LPS-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Our findings align with these previous reports and highlight that Ct intervention reduced lipid deposition in the liver by downregulating PPARγ expression and upregulating AMPK, ATGL, HSL, and PPARα expression. This validates the results of our previous transcriptomic data and is consistent with the research of Kershaw et al [ 24 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings align with these previous reports and highlight that Ct intervention reduced lipid deposition in the liver by downregulating PPARγ expression and upregulating AMPK, ATGL, HSL, and PPARα expression. This validates the results of our previous transcriptomic data and is consistent with the research of Kershaw et al [ 24 , 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our previous study on C. tyrobutyricum revealed its considerable high gastrointestinal tolerance and anti-inflammatory effect. Given that Ct was also linked to modifications in the expression of genes associated with hepatic lipid metabolism, we suspect that Ct treatment could alleviate obesity [ 24 ]. The present study offered novel evidence regarding the significant mitigating effect of C. tyrobutyricum intervention in lipid metabolic disorders brought on by the high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although no statistical differences existed, the relative abundance of E. coli in the feces of diarrheal piglets was twice of that of healthy piglets. LPS is a classical virulence factor produced by E. coli that causes diarrhea 42 , 43 , and our KEGG functional analysis revealed that LPS biosynthesis was significantly higher in diarrheal newborn piglets than in healthy newborn piglets. The Fusobacteria are a small group of Gram-negative bacteria, of which Fusobacterium are commonly found in the digestive tract of humans and animals.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Clostridium can inhibit the release of the proinflammatory factor IL-17 through short-chain fatty acids (SCFAs), thereby reducing the differentiation of Th1 and Th17 cells ( 39 , 40 ). The mechanism by which SCFAs regulate T-cell differentiation includes the mTOR pathway, G-protein-coupled receptor signaling, and epigenome remodeling to promote Treg cell differentiation.…”
Section: Differentiation and Regulation Of Th17 Cellsmentioning
confidence: 99%